2023
DOI: 10.3390/biom13060980
|View full text |Cite
|
Sign up to set email alerts
|

Synuclein Proteins in Cancer Development and Progression

Lucía C. Zanotti,
Florencia Malizia,
Nahuel Cesatti Laluce
et al.

Abstract: Synucleins are a family of small, soluble proteins mainly expressed in neural tissue and in certain tumors. Since their discovery, tens of thousands of scientific reports have been published about this family of proteins as they are associated with severe human diseases. Although the physiological function of these proteins is still elusive, their relationship with neurodegeneration and cancer has been clearly described over the years. In this review, we summarize data connecting synucleins and cancer, going f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…Due to the extensive research on PD, studies on the functions of α-synuclein often focus on neurons. However, it is intriguing to note that α-synuclein is highly expressed not only in neurons but also in cells of the hematopoietic system and certain malignant tumors (Araki et al 2018 ; Zanotti et al 2023 ). At this stage, definitive conclusions cannot be drawn.…”
Section: Physiological Functions Of α-Synuclein In Pd Pathogenesismentioning
confidence: 99%
“…Due to the extensive research on PD, studies on the functions of α-synuclein often focus on neurons. However, it is intriguing to note that α-synuclein is highly expressed not only in neurons but also in cells of the hematopoietic system and certain malignant tumors (Araki et al 2018 ; Zanotti et al 2023 ). At this stage, definitive conclusions cannot be drawn.…”
Section: Physiological Functions Of α-Synuclein In Pd Pathogenesismentioning
confidence: 99%
“…In addition to its role in PD, αS has been implicated in the pathology of various cancers [93,94]. It's been observed that elevated levels of αS could influence tumor growth and metastasis in particular cancer types, including breast cancer and colorectal cancer [95].…”
Section: Exploring Genetic Intersections: Parkinson's Associated Gene...mentioning
confidence: 99%
“…Cooperates with mGluR5 and γ-synuclein [11]. Involved in autophagy, mitochondrial metabolism, and ROS generation [12]. Regulates pro-and antiapoptotic processes [13].…”
Section: Synucleins α-Synucleinmentioning
confidence: 99%
“…Accumulation of misfolded α-synuclein oligomers increases vulnerability of neurons to dopamine-induced cell death. Affects mitochondrial metabolism, autophagy, and the generation of ROS [12].…”
Section: Synucleins α-Synucleinmentioning
confidence: 99%
See 1 more Smart Citation